Opportunity cost for early treatment of Chagas disease in Mexico. - Janine M Ramsey; Miguel Elizondo-Cano; Gilberto Sanchez-González; Adriana Peña-Nieves; Alejandro Figueroa-Lara (Public Library of Science (PLoS), 2014)
BACKGROUND: Given current neglect for Chagas disease in public health programs in Mexico, future healthcare and economic development policies will need a more robust model to analyze costs and impacts of timely clinical attention of infected populations. METHODOLOGY/PRINCIPAL FINDINGS: A Markov decision model was constructed to simulate the natural history of a Chagas disease cohort in Mexico and to project the associated short and long-term clinical outcomes and corresponding costs. The lifetime cost for a timely diagnosed and treated Chagas disease patient is US$ 10,160, while the cost for an undiagnosed individual is US$ 11,877. The cost of a diagnosed and treated case increases 24-fold from early acute to indeterminate stage. The major cost component for lifetime cost was working days lost, between 44% and 75%, depending on the program scenario for timely diagnosis and treatment. CONCLUSIONS/SIGNIFICANCE: In the long term, it is cheaper to diagnose and treat chagasic patients early, instead of doing nothing. This finding by itself argues for the need to shift current policy, in order to prioritize and attend this neglected disease for the benefit of social and economic development, which implies including treatment drugs in the national formularies. Present results are even more relevant, if one considers that timely diagnosis and treatment can arrest clinical progression and enhance a chronic patient's quality of life.